2010
DOI: 10.1007/s00586-010-1523-6
|View full text |Cite
|
Sign up to set email alerts
|

The Edwin Smith papyrus: a clinical reappraisal of the oldest known document on spinal injuries

Abstract: Dating from the seventeenth century b.c. the Edwin Smith papyrus is a unique treatise containing the oldest known descriptions of signs and symptoms of injuries of the spinal column and spinal cord. Based on a recent “medically based translation” of the Smith papyrus, its enclosed treasures in diagnostic, prognostic and therapeutic reasoning are revisited. Although patient demographics, diagnostic techniques and therapeutic options considerably changed over time, the documented rationale on spinal injuries can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(43 citation statements)
references
References 23 publications
0
37
0
1
Order By: Relevance
“…(van Middendorp et al, 2010). However, it is only since the latter half of the past century that ways to counteract the effects of spinal cord injury have been subjected to systematic studies in experimental animals (see Box 1).…”
Section: Introductionmentioning
confidence: 99%
“…(van Middendorp et al, 2010). However, it is only since the latter half of the past century that ways to counteract the effects of spinal cord injury have been subjected to systematic studies in experimental animals (see Box 1).…”
Section: Introductionmentioning
confidence: 99%
“…31). It has been suggested that the cases described in the papyrus predominantly concern patients who sustained their injuries during battles or construction work [19] . Ancient Egyptian surgeons classified spinal cord injuries into three broad categories: 1 An ailment that I will treat (favorable cases).…”
Section: Spinal Cord Injurymentioning
confidence: 99%
“…Historically, thoracic injuries to the spine have always predominantly been treated non-operatively [14]. Right up to the present day, there are publications which contemplate conservative treatment even for unstable fractures with neurological signs and symptoms [15].…”
Section: Conservative Managementmentioning
confidence: 99%